2007
DOI: 10.1196/annals.1422.053
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Overlap Syndrome

Abstract: Antiphospholipid syndrome (APS) can be either primary or secondary to autoimmune diseases, malignancies, infectious diseases, or drug-induced conditions. The aim of this study was to describe a novel overlap syndrome of APS and systemic sclerosis (SSc) in a case series. A retrospective review of medical files of hospitalized patients who were followed in two rheumatology clinics in Israel for the diagnosis of SSc and APS was sought. A MEDLINE search was performed for reports of APS/SSc overlap syndrome. Five p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…Recent evidence suggests that antiphospholipid antibodies, which alter the regulation of hemostasis and induce the activation of complement (83), are detected in several autoimmune disorders (84). They are recognized as a group of antibodies directed not only toward phospholipids such as cardiolipin, β 2 glycoprotein I ( β 2GPI), but also toward lupus anticoagulant antibodies, and antiphosphatidylserine-prothrombin complex antibodies that are detectable in SSc patients (67,69).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that antiphospholipid antibodies, which alter the regulation of hemostasis and induce the activation of complement (83), are detected in several autoimmune disorders (84). They are recognized as a group of antibodies directed not only toward phospholipids such as cardiolipin, β 2 glycoprotein I ( β 2GPI), but also toward lupus anticoagulant antibodies, and antiphosphatidylserine-prothrombin complex antibodies that are detectable in SSc patients (67,69).…”
Section: Resultsmentioning
confidence: 99%
“…SSc patients with aCL/a β 2GPI antibodies are more likely to develop microvascular dysfunction (pulmonary arterial hypertension, digital infarcts) and macrovascular impairment (69). Next, there is a strong correlation between the presence of aCL and pulmonary hypertension and the possibility that aCL/a β 2GPI and lupus anticoagulant antibodies may increase local production of endothelin and cause pulmonary hypertension (84). Also, patients with anti-PS-PT antibodies may represent a unique group of SSc patients with peripheral ischemia and lung disease, but these antibodies have not been found to be associated with severity of skin disease (86).…”
Section: Resultsmentioning
confidence: 99%
“…Minatani et al previously reported the first presentation of this overlap syndrome in a male patient [4]. One case series with five female patients [5] and other three cases of female patients [6–8] were also reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although cases of antiphospholipid (APL) syndrome have been described in a patient with scleroderma [259][260][261], the role of APL antibodies in the pathogenesis of the disease is not fully defined. Anticardiolipin antibodies (aCL) have been detected in about 4.8-45.5% of patients with scleroderma [262][263][264][265][266][267][268][269][270].…”
Section: Antiphospholipidsmentioning
confidence: 99%